Secured asynchronous-logic cryptography circuits to countermeasure against side-channel attack - Ng, Jun Sheng (Nanyang Technological University, 2024)
This thesis pertains to the investigation of asynchronous-logic design techniques as a countermeasure against the side-channel attack (SCA), i.e., an attack that exploits the secret key of cryptographic devices by analyzing their physical leakage information (e.g., power and electromagnetic). The goal is to design secure cryptographic devices that are highly resistant to SCA by leveraging asynchronous-logic (async-logic) design techniques. Thereafter, the proposed async-logic cryptographic devices are comprehensively evaluated with various SCA attacking models to validate their SCA resistance level in terms of measurement-to-disclosure (MTD), i.e., the minimum number of measurements to disclose the secret key. This thesis presents four proposed research works, summarized as follows.